Kebijakan Hilirisasi Mineral : Policy Reform untuk Meningkatkan Penerimaan Negara - Ika, Syahrir (Badan kebijakan Fiskal, 2017)
Indonesian mining sectors have not been optimally managed to raise budget income and bring public welfare. Main problem is laid on while Government give its concern more to upstream than to downstream management policy which gives low value added. Government has reformed its mining management by switching from upstream to downstream. This mining reform is shown in Law Number 4/2009 on Mineral and Batubara. However, the implementation is facing some technical and financial challenges. This study elaborates how urgent the ‘downstream policy’ is. Author also tries to portray the implementations and challenges Government faces, and recommend several steps needed to be taken. On the conclusion, the author gives suggest that Government needs to: (i) revise the Law Number 44/2009 as a better option compared to release several Government Regulation that proven not solve the problem; (ii) encourage some efforts to integrating downstream industries for their potentials to budget revenue; and (iii) support strategic alliance among state enterprises in order to act as downstream pioneers.